The importance of internationalization strategy for innovation in Portuguese firms - Durão, Natércia (2020)
Innovation and internationalization seem to be vital strategies for the survival and growth of companies facing an increasingly competitive global environment. The twoway link between these two factors has become a topic of interest among researchers. Although innovation and internationalization are highly related activities, the role played by innovation in the internationalization process of firms has been analysed by internationalization, others consider that innovation can be a consequence of internationalization process. Given the great importance of small and medium-sized enterprises (SMEs) for the growth of economies, part of literature has paid special attention to this kind of enterprises. The aim of this study is to explore the relationship between innovation and internationalization within Portuguese firms, in particular to analyse whether Portuguese entrepreneurs consider innovation as an important factor in the process of internationalisation. To achieve this goals, we will use descriptive and inferential data analysis techniques.